2020
DOI: 10.1101/2020.05.29.123018
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vivo recellularization of xenogeneic vascular grafts decellularized with high hydrostatic pressure method in a porcine carotid arterial interpose model

Abstract: Autologous vascular grafts are widely used in revascularization surgeries for small caliber targets. However, the availability of autologous conduits might be limited due to prior surgeries or the quality of vessels. Xenogeneic decellularized vascular grafts from animals potentially substitute for autologous vascular grafts. Decellularization with high hydrostatic pressure (HHP) is reported to highly preserve extracellular matrix (ECM) which would be feasible for recellularization and vascular remodeling after… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Based on this result, it was suggested that drying out the luminal surface of the decellularized aorta may lead to neointima hyperplasia. This in vitro result correlates with a previous in vivo study that showed vessel occlusion when the intima were dried before implantation [ 23 ]. As for the HHP tunica media, initial adhesion of HUVECs was observed, but they were shed during cell culturing.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on this result, it was suggested that drying out the luminal surface of the decellularized aorta may lead to neointima hyperplasia. This in vitro result correlates with a previous in vivo study that showed vessel occlusion when the intima were dried before implantation [ 23 ]. As for the HHP tunica media, initial adhesion of HUVECs was observed, but they were shed during cell culturing.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that the anti-coagulability was higher for HHP-treated tunica-intima and lower for decellularized aortas with disordered luminal surface structures (HHP 90°C tunica-intima, HHP 30 min dried tunica-intima, HHP tunica-media). Previously, it was reported that damaging the luminal surface of grafts by drying decreased graft patency after transplantation [ 23 ]. Therefore, this in vitro result correlates with the in vivo results and indicates that the more similar the luminal surface structure is to the native aorta, the higher the anti-coagulant property.…”
Section: Discussionmentioning
confidence: 99%
“…To maintain the extracellular matrices (ECMs) after decellularization with a sufficient efficiency of decellularization and microorganism removal, we developed an original physical decellularization method called a high hydrostatic pressure (HHP) method [12][13][14] . We recently confirmed that implantation of xenogeneic HHP-decellularized vascular tissue in a large animal model could confer endothelial cell migration and maintenance of endothelium in the implanted vascular tissue 15 . However, thromboembolism occurred after implantation when the inner surface of the vascular grafts was damaged by dry conditions during surgery, possibly owing to the absence of an intact endothelial cell layer before implantation; this encouraged us to address this problem for the broader application of this technology.…”
mentioning
confidence: 69%
“…To maintain the extracellular matrices (ECMs) after decellularization with a su cient e ciency of decellularization and microorganism removal, we developed an original physical decellularization method called a high hydrostatic pressure (HHP) method [12][13][14] . We recently con rmed that implantation of xenogeneic HHP-decellularized vascular tissue in a large animal model could confer endothelial cell migration and maintenance of endothelium in the implanted vascular tissue 15 . However, thromboembolism occurred after implantation when the inner surface of the vascular grafts was damaged by dry conditions during surgery, possibly owing to the absence of an intact endothelial cell layer before implantation; this encouraged us to address this problem for the broader application of this technology.…”
Section: Introductionmentioning
confidence: 99%